Dye-decolorizing activity in isolated yeasts from the ecoregion of Las Yungas (Tucumán, Argentina) - Pajot, Hipolito Fernando (2007)
Sixty-three yeast isolates obtained from samples of Laurel del monte (Phoebe porphyria) and underlying soils from Las Yungas forests (Tucumán, Argentina) were compared on their ability for textile dye decolorization. Seventeen isolates showed the highest decolorization ability on agar plates containing Vilmafix® Yellow 4R-HE, Vilmafix® Red 7B-HE (Vi–R), Vilmafix® Blue RR-BB (Vi–B) and Vilmafix® Green RR-4B, either alone or as a mixture. Screening in liquid media supplemented with dyes led to the five outstanding isolates: 2023, 2184, 2030, 2118 and 2014 showing dye removal values as high as 87.9–98.7% for Vi–B and 89.8–94.5% for Vi–R after 72 h of cultivation under aerobic conditions. Highest specific (3.06 and 2.43 mg g−1 h−1 for Vi–B and Vi–R, respectively) and volumetric (5.39 and 4.14 mg l−1 h−1 for Vi–B and Vi–R, respectively) decolorization rates were achieved with isolate 2023. Almost colorless biomass recovered after decolorization, supernatant UV–vis spectra and the presence of extracellular oxidative factors suggested that biodegradation mechanisms may be involved in decolorization. Selected isolates were identified according to classical and molecular procedures and were clumped into group 2118-2014 corresponding to Trichosporon multisporum (100% similarity) and group 2023-2184-2030, closely related to T. laibachii (98.9% similarity).